CAPITAL MARKET REACTION BEFORE AND AFTER THE ANNOUNCEMENT OF THE FIRST CASE OF COVID-19 IN INDONESIA - Sarlina Sari (Teunuleh Publisher, 2021)
This study aims to determine the differences in abnormal return, frequency of trade, and market capitalization before and after the informations regarding the first reporting of COVID-19 in Indonesia on the Indonesia Stock Exchange. The research population is all companies that entered into Top Leadings in Market Capitalization companies on the Stock Exchange in the period Februari – April 2020, namely as many as 50 companies. The sample in this study was taken using the census method, meaning that the number of samples taken was equal to the number of members of the population. To test the hypothesis of this study using a paired sample test. The observation began 30 days before the event and 30 days after the event. This study uses quantitative research in the comparative method. The finding show that the information caused the market was approved. This is proven by the existence of significant results in daily tests on the indicators. The results were also significant in the combined abnormal return test and the combined market capitalization test. The trade comparison test results show a significant difference which means there was a market-panic towards trading activities after the event that caused some frequency differences, before and after the event in terms of trade transactions. So, the results of this study indicate that there are differences in abnormal returns, frequency of trade, and market capitalization before and after the announcement of the informations regarding the first reporting of COVID-19 in Indonesia.